A SINGLE-CENTRE EXPERIENCE IN UTILIZATION OF MITOTANE AS AN ADJUVANT THERAPY FOR ADRENOCORTICAL CARCINOMA - H, Alyani; MA, Masliza Hanuni; MM, Nur Hidayah; M, Hussain; M, Nor Hisham (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Adrenocortical carcinoma (ACC) is a rare, aggressive tumour with an estimated incidence of ~0.5-2 per million/year. It may present with autonomous adrenal hormone excess or with symptoms caused by an abdominal mass. METHODOLOGY We report a case of a 55-year-old male who presented with left loin pain for a year, associated with loss of appetite, weight loss and fatigue. There were no symptoms and signs suggestive of cortisol or androgen excess. RESULT Initial abdominal CT demonstrated a large enhancing solid adrenal mass measuring 13.6 x 12.5 x 16.8 cm. One month following this finding, he was hospitalized for septic shock secondary to infected left adrenal mass and adrenal insufficiency (cortisol on inotropic support was 173 nmol/l). Other functional tests such as 24-hour urine metanephrines and ARR were within normal range. Open left adrenalectomy and left nephrectomy were performed. Intra operatively, a vascularized left adrenal tumour, size approximately 20 x 15 cm which ruptured with pus was noted. Tumour was seen infiltrating the upper and middle pole of the left kidney extending to the calices. Histopathological examination confirmed ACC with Ki-67 of 1%. The European Network for the Study of Adrenal Tumours (ENSAT) staging was TIII, N0, M0, Rx. After a multidisciplinary discussion, we agreed to initiate adjuvant mitotane therapy with a low threshold for radiotherapy. We started him on mitotane 500 mg TDS and increased this to 1 g TDS after a month. Glucocorticoid replacement with hydrocortisone was increased accordingly from 10 mg TDS to 20/20/10 mg TDS. He tolerated this dosing well with no adverse effects. Laboratory monitoring with FBC, RP, and LFT were all normal. Latest CT staging showed no residual tumour or any evidence of distant metastasis. CONCLUSION More than half of patients with ACC who have undergone complete removal of the tumour have a relapse risk, often with metastases. The current guideline advocates for the use of adjuvant mitotane therapy in patients without macroscopic residual tumour after surgery, but who have a perceived high risk of recurrence, as in our case.